(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Cultural diversity strongly influences dietary habits, nutrition perceptions, and health outcomes. Nutrition education lacking cultural awareness often fails to engage communities or sustain behaviour change. Drawing on frameworks such as cultural competence, community-based participation, and culturally responsive pedagogy, it shows how tailoring interventions to local languages, food preferences, and traditions enhances effectiveness. Culture is presented not as a barrier but as a foundation for building trust, relevance, and empowerment in nutrition education, with recommendations for educators and policymakers to incorporate cultural adaptation at every stage.